Synthesis and degradation mechanism of renally excretable gold core–shell nanoparticles for combined photothermal and photodynamic therapy. Issue 3 (21st December 2022) - Singh, Barkha; Patnaik, Chetna; Bahadur, Rohan; Gandhi, Mayuri; De, Abhijit; Srivastava, Rohit
Abstract : Photothermal therapy using Zein gold nanoshell as a potent therapeutic aproach in the treatment of tumors.  Abstract : Photothermal therapy (PTT) has emerged as a very potent therapeutic approach in the treatment of tumors. Gold nanoparticles have gained considerable scientific interest as a photosensitizer due to their absorbance in the near-infrared regions. However, their biodegradation and excretion from the body is a challenge. Various biodegradable systems consisting of liposomes and polymers have been synthesized, but their precise manufacturing and decomposition mechanisms have not yet been explored. Using zein nanoparticles as a template, we have fabricated a glutathione-functionalized gold core shell type of formulation. The scalability of the one-step seedless gold coating process is also reported. The synthesis procedure of these tunable nanoparticles is understood with TEM. The thermal degradation of the material under the physiological conditions is thoroughly examined using UV and TEM. In vitro PTT effectiveness on breast cancer cells is assessed after an extensive in vitro toxicity research. The mechanism of cell death is studied using ROS and cell cycle analysis. The material exhibited good efficacy as a PTT agent in mice and showed non-toxicity up to 14 days. The renal clearance study of the material in mice shows its disintegration into renal clearable minute gold seeds. All the findings suggest biodegradable glutathione-functionalized gold core–shell nanoparticles as potential photothermal cancer treatment agents.